Potent inhibition of Epstein-Barr virus by phosphorothioate oligodeoxynucleotides without sequence specification. - Yao, G Q (1993)
We found that 28-mer phosphorothioate oligodeoxynucleotides (S-oligos) with and without sequence specificity complementary to Epstein-Barr virus (EBV) genes are potent inhibitors of EBV replication in cell culture. The decrease in the amount of EBV DNA, the activity of intracellular viral DNA polymerase, and virus production were dose dependent, with a 90% inhibitory dose of approximately 0.5 microM. No inhibition of cell growth was observed with the S-oligos at concentrations up to 20 microM. The mechanism of action appears to be the inhibition of EBV DNA synthesis. The reversibility of anti-EBV action is dependent on the dose and duration of drug exposure. S-oligos should be considered a new class of anti-EBV agents.